Getting Ahead While Getting Along: Followership as a Key Ingredient for Shared Leadership and Reducing Team Conflict - Baird, Noelle; Benson, Alex J. (Frontiers in Psychology, 2022)
Followership and leadership provide two distinct but complementary sets of behaviors that jointly contribute to positive team dynamics. Yet, followership is rarely measured in shared leadership research. Using a prospective design with a sample of leaderless project teams, we examined the interdependence of leadership and followership and how these leader-follower dynamics relate to relationship conflict at the dyadic and team level. Supporting the reciprocity of leader-follower dynamics, social relations analyses revealed that uniquely rating a teammate higher on effective leadership was associated with being rated higher by that same person on effective followership. Additionally, team members with a reputation as an effective leader also tended to be viewed as an effective follower. As expected, team levels of leadership were tightly linked to team levels of followership. Connecting these results to relationship conflict at the dyadic level, we found that uniquely rating someone as an effective follower or an effective leader would decrease the likelihood of experiencing interpersonal conflict with that person and that having a reputation for effective followership or effective leadership relates negatively to being viewed as a conflict hub within the team. Finally, effective followership was significantly negatively related to team levels of conflict, but we did not find a significant relation between effective leadership and relationship conflict at the team level. Our results highlight that followership is not only a necessary ingredient for high levels of shared leadership to exist within a team, but it underpins more functional team interactions.